2021
DOI: 10.1101/2021.09.17.460868
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered interactions between circulating and tissue-resident CD8 T cells with the colonic mucosa define colitis associated with immune checkpoint inhibitors

Abstract: Therapeutic blockade of co-inhibitory immune receptors PD-1 and CTLA-4 has revolutionized oncology, but treatments are limited by immune-related adverse events (IRAEs). IRAE Colitis (irColitis) is the most common, severe IRAE affecting up to 25% of patients on dual PD-1 and CTLA-4 inhibition. Here, we present a systems biology approach to define the cell populations and transcriptional programs driving irColitis. We collected paired colon mucosal biopsy and blood specimens from 13 patients with irColitis, 8 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 118 publications
1
20
1
Order By: Relevance
“…In melanoma patients, it has been shown that untreated patients with untreated metastatic disease have decreased CD14 + monocytes in the peripheral blood compared to healthy controls, a finding recapitulated in our analysis, and that the phenotypes of these monocytes may be a predictor of disease response to CBI [ 22 ]. Although limited data exists thus far on monocyte dynamics in tissue during irAEs, early analyses of colitis patients point to an influx of monocytes with a phenotype resembling that of the CD14 + population reported here [ 23 ]. While additional studies are needed, the existing data clearly suggests an important role for these monocyte populations in irAE development.…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma patients, it has been shown that untreated patients with untreated metastatic disease have decreased CD14 + monocytes in the peripheral blood compared to healthy controls, a finding recapitulated in our analysis, and that the phenotypes of these monocytes may be a predictor of disease response to CBI [ 22 ]. Although limited data exists thus far on monocyte dynamics in tissue during irAEs, early analyses of colitis patients point to an influx of monocytes with a phenotype resembling that of the CD14 + population reported here [ 23 ]. While additional studies are needed, the existing data clearly suggests an important role for these monocyte populations in irAE development.…”
Section: Discussionmentioning
confidence: 99%
“…As our understanding of irAE mechanisms in patients evolve, it will help to identify which, if any, animal models most accurately recapitulate organ-specific irAEs in patients and inform the next generation of irAE models that can be used to test the relationship between irAE therapeutics and antitumor efficacy. 53 As T cells are thought to be central to the antitumor responses driven by ICIs 4,9 and are found to predominate the immune cell infiltrate in irAE tissue biopsies across organ systems, 8,10,11,13,16,23,38,[54][55][56][57] many studies have looked at the relationship of T cells in irAEs and paired tumors. While central and peripheral tolerance mechanisms cause many autoreactive T cells to become anergic or die during Tcell development, autoreactive T cells are still commonly found in humans 14,44 and are anticipated to play a role in the development of irAEs.…”
Section: The Molecul Ar Rel Ati On S Hip B E T Ween Irae S and Antitu...mentioning
confidence: 99%
“…Depending on the drugs and doses used, 66%–96% of patients will have side effects from ICIs, and 7%–59% of patients will experience severe irAEs, which are also commonly referred to as “high‐grade” irAEs 6,7 . While the prevailing hypothesis in the field suggests that irAEs are due to a loss of self‐tolerance, 8,9 the mechanistic drivers of irAEs are only beginning to emerge 10–16 . As murine tumor models typically utilized to study ICI efficacy do not develop severe irAEs, 17 insights into the relationship between irAEs and antitumor immunity have been guided by clinical observations and translational research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These T cells are activated (expressing IFNG and HAVCR2 ), proliferative, and are more clonal 38,39 . Phenotypically similar activated PDCD1 hi CXCL13 + CD8A + T cells have been found to be enriched in irAE‐colitis, 40 again expressing high IFNG and HAVCR2 but, in contrast to those in irArthritis, also coexpressing Th17 cytokines IL17A and IL26 . The same population is enriched in checkpoint inhibitor pneumonitis, again overexpressing IL17A and IFNG but also here expressing CSF2 41 .…”
Section: Immune Phenotyping Of Rheumatic Iraesmentioning
confidence: 99%